Human Fungal Infections in Kuwait—Burden and Diagnostic Gaps - Alfouzan, Wadha (J Fungi (Basel), 2020)
Fungal infections are an increasingly important public health issue, yet accurate statistics on fungal burden worldwide and in Kuwait are scarce. Here we estimate the incidence and prevalence of fungal infections in Kuwait. Population statistics from 2018 collected by the Public Authority for Civil Information were used, as well as data from the Ministry of Health. A literature search for Kuwait data on mycotic diseases and population at risk (chronic obstructive pulmonary disease, HIV infection/AIDS, cancer, and transplant patients) was conducted. The population in 2018 was estimated at 4,226,920 million people: 1,303,246 million Kuwaitis and 2,923,674 million expatriates. We determined the annual burden of serious fungal infections number (per 100,000) from high to low based on earlier reported fungal rates for populations at risk: recurrent Candida vaginitis 54,842 (2595); severe asthma with fungal sensitisation 10,411 (246); allergic bronchopulmonary aspergillosis, 7887 (187); chronic pulmonary aspergillosis 995 (21.3); invasive aspergillosis 704 (16.7); fungal keratitis 654 (15.5); candidaemia 288 (6.8); Candida peritonitis 63 (3.5) and oesophageal candidiasis in HIV 33 (0.8). Besides identifying rising new risk groups and expanding reports on antifungal resistance, surveillance programs and further epidemiological studies are needed to achieve more precise assessments of fungal disease epidemiology and correlated morbidity and mortality.